Biomedical composites : materials, manufacturing, and engineering - Davim, J. Paulo (Advanced composites ;, 2014)
"Composite materials are engineered materials, made from two or more constituents with significantly different physical or chemical properties which remain separate on a macroscopic level within the finished structure. Due to their special mechanical and physical properties they have the potential to replace conventional materials in various fields such as the biomedical industry"--Publisher's description.